(untitled) (Bangladesh Journal of Medical Education, 2019)
This cross sectional descriptive study was conducted to explore the dietary habits and body weight status of undergraduate medical students of Bangladesh and their influence on academic performance. The study period was from July 2017 to June 2018. The sample size was 907. Medical colleges were selected purposively and convenience sampling technique was adopted for data collection. The study was carried out among the students of 3rd and 4th phase MBBS course of five public and three non-government medical colleges of Dhaka and outside Dhaka. Academic performance was determined by the results of professional examinations and class attendance. A self-administered structured questionnaire was used. Among the respondents medical students 330 (36.5%) were males and 575 (63.5%) were females. Descriptive statistics were used to identify the dietary practices of the students. Chi squared test and unpaired t test were done to examine the influence of diets and BMI on academic performance. The study revealed that 535 (59.9%) students took three main meals regularly. Breakfast was the commonest meal skipped among 230 (24%) students altogether. Among the respondents students, 652 (73.2%) took first class proteins daily, 398 (44.8%) vegetables daily and only 85 ((9.6%) students took fruits daily. 661 (74.4%) of the students belonged to healthy BMI group and 73 (8.2%) students were underweight, 12 (1.4%) students were obese and 3 (0.3%) were morbidly obese. Gender wise there was no significant difference of BMI. The study further revealed that students who took first class protein daily had better performance in the professional examinations. Skipping of breakfast and consumption of vegetable and fruits did not affect students’ academic performance. The students with healthy BMI had higher percentage in class attendance than the overweight students. The study recommended that steps to be taken to implement healthy dietary practices among the medical students for positive influence on academic performance. Bangladesh Journal of Medical Education Vol.10(2) 2019: 6-11